Museum of Modern and Contemporary Art in Bandung with Contextual Architecture Approach - Okki Nurrisman; Nutrian Galupamudia; Arief Perdana Putra (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
The delivery of art education in an interesting way is a learning method that is favored by many people. In Indonesia, especially in Bandung, there are still many people who cannot develop their artistic talents. This design aims to develop art knowledge for visitors, especially modern and contemporary art, and also to express the artistic spirit of the community through expression spaces. This design approaches design with contextual architecture where this building can adjust to the surrounding environment, surrounding buildings, and historical values in the area. This design is carried out by searching for literature and precedent studies which will be used as a reference in designing and analyzing problems, then a comparative study is made to create harmony with the function of the building. This design is expected to be a design picture that can be developed further in the future.